Effects of Splitting Airfoil’s Aspect Ratio on the Control of Separation and Loss Distribution in a Distortion Generator - M. Hassani; M. Bazazzadeh; M. D. Manshadi (International Journal of Aerospace Engineering)
The effects of aspect ratio (AR: opposite diameter to width) reduction on the total pressure loss distribution of horizontally arranged splitting airfoils are investigated experimentally and numerically. The array arrangement of airfoils is proposed as a novel distortion generator mechanism. The upgrade feasibility study of the single airfoil loss repeatability in combined pattern was the aim of the present research. Modification of 90° splitting airfoil as a representative of the airfoils category with AR>1 was a corrective approach to eliminate or delay the downstream wake axis rotation destructive effects on the combined loss predictability. The results of the modified airfoil (single and multiple arrangements) wake simulations based on hybrid turbulence model demonstrate a good agreement with wind tunnel measurements. It was observed that the aspect ratio reduction below the limiting value of “1” for selected opening angle provides the quasi-2D behavior of downstream flow structure related to AR<1 airfoil category along with relatively higher value of loss related to AR>1 category. Elimination of the side separation for modified 90° airfoil and the resulting similarity of maximum loss lobes positioning in arrangement of airfoils lead to the reduction of combined flow structure complexity and the improvement of loss predictability. It has appeared that combined loss pattern of the triple arrangement of the airfoils can be reconstructed from dual arrangement, and it can be reproduced from a single pattern in a hierarchical process. Concerning the maximum loss coefficient “values,” an overprediction of velocity recovery rate was observed in simulation results at the fully developed wake region that led to approximately 15% lower maximum loss values in comparison with the experiments.